Predicting pregnancy outcomes from homocysteine level: an evidence from a North Indian study - Chamotra, Shaina; Pathania, Kushla; Verma, S. K.; Chaudhary, Ankit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy are a major cause of adverse pregnancy outcomes. Though the etiology of spectrum of vascular disorders of pregnancy is still not understood completely, yet abnormally elevated homocysteine level has been implicated in the causal pathway and pathogenesis. Hyperhomocysteinemia has been significantly associated with increased risk of poor maternal and foetal outcomes in terms of PIH, abruption, IUGR, recurrent pregnancy loss, intrauterine death and prematurity. Methods: The present prospective study was conducted among 180 pregnant women (57 exposed and 123 non exposed) in Kamla Nehru State Hospital for Mother and Child, IGMC Shimla, Himachal Pradesh with an objective of determining association of abnormally elevated homocysteine level in pregnancy and adverse pregnancy outcomes. Socio-demographic, clinical, biochemical including homocysteine level, laboratory, ultrasonographic parameters and foeto-maternal outcomes of pregnancy of all the participants were documented. Results: The mean homocysteine level of exposed group (23.26±10.77 µmol/L) was significantly higher than the unexposed group (8.99±2.47 µmol/L). Among hyperhomocysteinemic subjects, 10.5% had abruption, 15.8% had PRES and 8.7% PPH which was significantly higher than normal subjects. Similarly, patients with homocysteinemia had significantly higher proportion (21.3%) of poor Apgar score, more (41.9%) NICU admissions and higher frequency (4.7%) of meconium aspiration syndrome. Conclusions: The present study generates necessary evidence for associating abnormally elevated homocysteine levels with pregnancy related hypertensive ailments and adverse pregnancy outcomes. It further demands the need of robustly designed studies and trials to further explore the phenomenon. Moreover, it emphasizes on a simple and timely intervention like estimating the much-neglected homocysteine levels during pregnancy which can definitely contribute in predicting and preventing adverse perinatal outcomes.